Stakeholder management as a predictor of CEO compensation: main effects and interactions with financial performance - Coombs, Joseph E.; Gilley, K. Matthew (Strategic Management Journal, 2005)
Abstract We test the effects of stakeholder management on CEOs' salaries, bonuses, stock options, and total compensation. We also examine the extent to which the interaction of stakeholder management and financial performance determines compensation. Using a longitudinal database of 406 Fortune 1000 firms, our results suggest that stakeholder management is relevant to boards of directors when setting CEO compensation. Specifically, we found a significant, negative main effect of stakeholder management on CEO salaries. Further, we found that stakeholder management typically reduces the rewards CEOs may get for increasing levels of financial performance. In tandem, these results indicate that CEOs may jeopardize their personal wealth by pursuing stakeholder‐related initiatives. Copyright © 2005 John Wiley & Sons, Ltd.